Original papersPlasma lipoprotein (a) levels in patients with slow coronary flow - Yucel, Habil; Dogan, Abdullah; Altinbas, Ahmet; Akcay, Salaheddin; Icli, Atilla; Ceyhan, Betul Mermi (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : Slow coronary flow (SCF) is a microvascular disorder characterized by delayed opacification of coronary vessels with normal coronary angiogram. It may be due to endothelial dysfunction and diffuse atherosclerosis. Lipoprotein(a) [Lp(a)] is related to cardiovascular events. Plasma Lp(a) levels have not been studied previously in SCF patients. Aim: We investigated plasma Lp(a) and fibrinogen levels, and their relation to coronary flow rate in patients with SCF. Material and methods: This cross-sectional study included 50 patients with SCF and 30 age- and sex-matched controls who had normal coronary arteries and normal flow. Coronary flow rates of patients and controls were counted with the thrombolysis in myocardial infarction (TIMI) frame count. Plasma Lp(a) and fibrinogen levels were measured in SCF patients and controls, with routine biochemical tests. Results: There were no significant differences between the two groups with respect to plasma Lp(a) (21 mg/dl vs. 14 mg/dl, p = 0.11) and fibrinogen (278 mg/dl vs. 291 mg/dl, p = 0.48) levels. The TIMI frame count was not correlated with plasma Lp(a) (r = 0.13, p = 0.25) or fibrinogen (r = –0.14, p = 0.28) levels. Conclusions : Our results show that there is no significant association between SCF and Lp(a) and fibrinogen levels.